The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s11999-017-5510-7
|View full text |Cite
|
Sign up to set email alerts
|

Version Correction via Eccentric Reaming Compromises Remaining Bone Quality in B2 Glenoids: A Computational Study

Abstract: This computational study of eccentric reaming of the glenoid before TSA quantitatively showed glenoid bone quality is sensitive to version correction via simulated eccentric reaming. The bone density results of our study may benefit surgeons to better plan TSA on B2 glenoids needing durable bone support, and help to clarify goals for development of precision surgical tools.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 29 publications
3
24
0
Order By: Relevance
“…Chevalier et al used micro finite element models based on micro-CT scans of cadaveric scapulae to evaluate the influence of bone volume fraction, trabecular anisotropy and cortical thickness on stress within the periprosthetic bone and cement mantle [ 19 ]. In a further computational study, Chen et al measured the glenoid BMD in HU after simulated eccentric reaming for version correction of Walch B2 glenoids [ 18 ]. They analyzed BMD in five adjacent 1-mm layers under the reamed glenoid surface, and concluded that increased version correction resulted in gradual depletion of high-quality bone from the anterior regions of B2 glenoids.…”
Section: Discussionmentioning
confidence: 99%
“…Chevalier et al used micro finite element models based on micro-CT scans of cadaveric scapulae to evaluate the influence of bone volume fraction, trabecular anisotropy and cortical thickness on stress within the periprosthetic bone and cement mantle [ 19 ]. In a further computational study, Chen et al measured the glenoid BMD in HU after simulated eccentric reaming for version correction of Walch B2 glenoids [ 18 ]. They analyzed BMD in five adjacent 1-mm layers under the reamed glenoid surface, and concluded that increased version correction resulted in gradual depletion of high-quality bone from the anterior regions of B2 glenoids.…”
Section: Discussionmentioning
confidence: 99%
“…However, 10° and higher of version correction resulted in a significant loss of quality of glenoid bone, specifically in the anterior region. 56 These results indicate that other options are needed to address bone deficiency and restore joint line in such situations. Some authors proposed use of humeral head autograft with all-poly glenoid to correct this retroversion.…”
Section: Metal-backed Glenoid (Mbg)mentioning
confidence: 98%
“…To our knowledge, our study is the rst to quantitatively assess the impact of preoperative glenoid BMD in 3D on glenoid implant survivalmore speci cally aseptic glenoid looseningin aTSA. Most previous studies have evaluated the quality of the glenoid bone support using CT datasets (either micro-or conventional CT), but only few have correlated their ndings with clinical and radiological outcomes [17][18][19]22]. Our semi-automated quantitative measurement method based on a computerized 3D scapular reconstruction model has proven its reliability and already helped improving glenoid implant positioning [43].…”
Section: Discussionmentioning
confidence: 99%